Download presentation

Presentation is loading. Please wait.

Published byEmil Gibbs Modified over 9 years ago

1
1 Press Ctrl-A ©G Dear 2008 – Not to be sold/Free to use Binomial Products Stage 6 - Year 11 Mathematic (Preliminary)

2
2 Binomial Products FOIL Method (a + b)(x + y) = Firsts, Outers, Inners, Lasts.

3
3 Binomial Products FOIL Method (a + b)(x + y) = Firsts, Outers, Inners, Lasts. ax

4
4 Binomial Products FOIL Method (a + b)(x + y) = Firsts, Outers, Inners, Lasts. ax+ ay

5
5 Binomial Products FOIL Method (a + b)(x + y) = Firsts, Outers, Inners, Lasts. ax+ ay + bx

6
6 Binomial Products FOIL Method (a + b)(x + y) = Firsts, Outers, Inners, Lasts. ax+ ay + bx+ by

7
7 Binomial Products FOIL Method (a + b)(x + y) = Firsts, Outers, Inners, Lasts. or Distributive Method (a + b)(x + y) = ax+ ay+ bx+ by

8
8 Binomial Products FOIL Method (a + b)(x + y) = Firsts, Outers, Inners, Lasts. or Distributive Method (a + b)(x + y) = ax+ ay + bx+ by a(x + y)

9
9 Binomial Products FOIL Method (a + b)(x + y) = Firsts, Outers, Inners, Lasts. or Distributive Method (a + b)(x + y) = ax+ ay+ bx+ by + b(x + y)a(x + y)

10
10 Binomial Products FOIL Method (a + b)(x + y) = Firsts, Outers, Inners, Lasts. or Distributive Method (a + b)(x + y) = = ax + ay + bx + by ax+ ay+ bx+ by + b(x + y)a(x + y)

11
11 Binomial Products Examples of Distributive Law (2x + 3)(3x + 2) =2x(3x + 2)+ 3(3x + 2) = 6x 2 + 4x+ 9x + 6 = 6x 2 + 13x + 6

12
12 Binomial Products Examples of Distributive Law (x - 5)(2x - 3) = x(2x - 3) - 5(2x - 3) = 2x 2 - 3x - 10x + 15 Common Mistake = 2x 2 - 13x + 15

13
13 Binomial Products Related Products (a + b)(x + y + z) = ax + ay + az + bx + by + bz (2x +3)(x + y - 2) = = 2x 2 + 2xy - 4x + 3x + 3y - 6 = 2x 2 + 2xy - x + 3y - 6 = 2x(x + y - 2)+ 3(x + y - 2) Example

14
14 Binomial Products Special Products (a + b) 2 =a 2 + 2ab + b 2 Proof (a + b) 2 = (a + b)(a + b) = a(a + b) + b(a + b) = a 2 + ab+ ab + b 2 = a 2 + 2ab + b 2

15
15 Binomial Products Special Products (a + b) 2 =a 2 + 2ab + b 2 Example (2x + 3) 2 = (2x) 2 + 2 x 2x x 3 + 3 2 = 4x 2 + 12x + 9 aa bb

16
16 Binomial Products Special Products (a - b) 2 =a 2 - 2ab + b 2 Proof (a - b) 2 = (a - b)(a - b) = a(a - b) - b(a + b) = a 2 - ab- ab + b 2 = a 2 - 2ab + b 2

17
17 Binomial Products Special Products (a - b) 2 =a 2 - 2ab + b 2 Example (3x - 2) 2 = (3x) 2 - 2 x 3x x 2 + 2 2 = 9x 2 - 12x + 4 aa bb

18
18 Binomial Products Special Products (a + b)(a -b) =a 2 - b 2 Proof (a + b)(a - b) = = a(a - b) + b(a - b) = a 2 - ab + ab - b 2 = a 2 - b 2

19
19 Binomial Products Special Products (a + b)(a -b) =a 2 - b 2 Example (2x + 3y)(2x - 3y) = = 4x 2 - 9y 2 aa bb (2x) 2 - (3y) 2 aa bb

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google